Challenges of the Internet of Things - Saleh, Imad; Ammi, Mehdi; Szoniecky, Samuel (Wiley-ISTE, 2019)
This book will examine the issues of IoT according to three complementary axes: technique, use, ethics. The techniques used to produce artefacts (physical objects, infrastructures), programs (algorithms, software) and data (Big data, linked data, metadata, ontologies) are the subject of many innovations as the field of IoT is rich and stimulating. Along with this technological boom, IoT uses colonize new fields of application in the fields of transport, administration, housing, maintenance, health, sports, well-being. ... Privileged interface with digital ecosystems now at the heart of social exchanges, the IoT develops a power to act whose consequences both good and bad make it difficult to assess a fair business.